Analysis of Fibrotic Plaques in Angiographic Manifest Cardiac Allograft Vasculopathy in Long-term Heart Transplanted Patients Using Optical Coherence Tomography. Issue 1 (23rd December 2021) - Orban, Madeleine; Dischl, Dominic; Müller, Christoph; Ulrich, Sarah; Petzold, Tobias; Rizas, Konstantinos; Orban, Martin W.; Braun, Daniel; Hausleiter, Jörg; Hagl, Christian; Mehilli, Julinda; Massberg, Steffen
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The development and progression of cardiac allograft vasculopathy documented by coronary angiography (CAVangio ) after heart transplantation (HTx) has prognostic relevance. Yet there are limited data regarding the role of concomitant intracoronary imaging in the presence CAVangio . In particular, atherosclerotic plaques might represent a potential target for prevention, but their impact on stenosis is understudied. Methods: We used high-resolution intracoronary optical coherence tomography (OCT) to quantify and compare findings of intimal hyperplasia (IH) and plaque morphologies in HTx patients (fibrotic plaque, lipid plaque, and calcified plaque). OCT findings were related to the presence of CAVangio as well as to the severity of stenosis. Results: We included 65 consecutive patients into analysis (66% with CAVangio, posttransplant interval 9.9 ± 7.6 y). Fibrotic, lipid, and calcified plaques were present in 41 (63.1%), 39 (60%), and 18 (27.7%) patients, respectively. In addition to IH, the presence of fibrotic, lipid, and calcified plaques was found to be associated with CAVangio . The prevalence of lipid plaque and quantitative measurements of fibrotic plaque increased with stenosis severity (lipid plaque, P < 0.001, maximal and mean fibrotic arc, P = 0.05 and P = 0.001, respectively). Receiver operating characteristic analysis showed that area under the curve of the fibrotic plaque parameter mean fibrotic arc (0.87, 95% confidence interval [0.76-0.99]; P = 0.002) was superior to area under the curve of intima parameters regarding CAVangio . The effect of mean fibrotic arc ( r = 0.52, P < 0.001) was relevant regarding stenosis severity. Conclusions: After a longer posttransplant interval, CAV findings in OCT included a combination of IH and atherosclerotic plaques. In addition to IH, the presence of fibrotic, lipid, and calcified plaques is associated with CAVangio . Further studies are warranted to evaluate if the in vivo screening for plaque progress, particularly of fibrotic plaque, could improve individual secondary prevention and outcome in HTx patients.